Training for employment in Western Europe and the United States - Shackleton, J.R. [Verfasser]; Clarke, Linda [Mitarbeiter]; Lange, Thomas [Mitarbeiter]; Walsh. Siobhan [Mitarbeiter] (Elgar, 1995)
"This book explores the economic analysis of training and relates it to the differing systems found in Western Europe and the United States. After an examination of the theoretical basis for increased emphasis on training, the authors present a comparative analysis of the different systems employed in Germany, France, the United Kingdom and the United States. A number of common issues and problems are discussed, such as the relationship between schooling and training, the role of continuing training, retraining for the unemployed, and the position of women and disadvantaged groups in the labour market. A central theme is the differing policies pursued by governments. While recognizing the common concern with potential market failure in training, the authors also draw attention to the poor record of government-funded training in practice and to the dangers of excessive intervention as a result of pressure group activity." (author's abstract, IAB-Doku) ((en)) Vergleichende theoretische und empirische Analyse der beruflichen Bildung und Weiterbildung bzw. Umschulung in drei westeuropäischen Ländern und den USA. (IAB)
Keywords: S 1 Stufen der Berufsbildung; G 1.2 Arbeitsmarkt; I 2.2.1 Westeuropa; I 2.3.2 Nordamerika; Berufliche Weiterbildung; Berufsbildung; Internationaler Vergleich; Arbeitsmarktpolitik; Erfolgskontrolle; Umschulung; Quantitative Angaben; Großbritannien; Frankreich; USA